Version Control System: A Review - Zolkifli, Nazatul Nurlisa; Ngah, Amir; Deraman, Aziz (Procedia computer science, 2018)
Version Control Systems (VCS) have been used by many software developers during project developments as it helps them to manage the source codes and enables them to keep every version of the project they have worked on. It is the way towards managing, organizing, and coordinating the development of objects. In Software Engineering, software developers need to collaborate with each other to develop a better project. Thus, VCS is very useful because it also supports a collaborative framework that makes it easy for software developers to work together effectively. Without VCS, collaboration is very challenging. This paper discusses the background and the related works about VCS that have been studied by researchers. The purpose of this paper is to convey the knowledge and ideas that have been established on VCS.